Frozen vs. Fresh Embryo Transfer dalam Program IVF: Sebuah Review Literatur tentang Implikasi terhadap Live Birth Rate dan Risiko Preeklampsia - Maharani Chikita; Azniah Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Infertility is a global health problem that has significant social and psychological impacts. Factors such as environmental and occupational factors, physical activity, and poor nutrition can increase the risk of infertility. Assisted reproductive technology (ART) is one of the main interventions used to treat infertility, with in vitro fertilization (IVF) being the most common method. In IVF, there are two methods of embryo transfer: frozen embryo transfer (FET) and fresh embryo transfer (ET). This study aims to compare the live birth rate between frozen and fresh embryo transfer in IVF programs and assess the risk of preeclampsia associated with both embryo transfer methods. A literature review was conducted by searching 20 scientific articles from PubMed, Google Scholar, and ScienceDirect using inclusion criteria and the PICO strategy and PRISMA flow chart. Inclusion criteria included publications from the last 10 years, English language, and human studies. The results showed that both methods produced comparable live birth rates (LBR) with FET slightly superior to ET, depending on the patient's condition and characteristics. On the other hand, there was a significantly increased risk of preeclampsia in FET, especially in patients using the artificial cycle protocol (AC-FET). The conclusion of this review is that FET and ET methods are effective in achieving pregnancy and there is an increased risk of preeclampsia in FET especially AC-FET which needs further consideration.